An extension to: Systematic assessment of commercially available low-input miRNA library preparation kits. Issue 9 (1st September 2020) - Heinicke, Fatima; Zhong, Xiangfu; Zucknick, Manuela; Breidenbach, Johannes; Sundaram, Arvind Y.M.; T. Flåm, Siri; Leithaug, Magnus; Dalland, Marianne; Rayner, Simon; Lie, Benedicte A.; Gilfillan, Gregor D.
ABSTRACT: High-throughput sequencing has emerged as the favoured method to study microRNA (miRNA) expression, but biases introduced during library preparation have been reported. We recently compared the performance (sensitivity, reliability, titration response and differential expression) of six commercially-available kits on synthetic miRNAs and human RNA, where library preparation was performed by the vendors. We hereby supplement this study with data from two further commonly used kits (NEBNext, NEXTflex) whose manufacturers initially declined to participate. NEXTflex demonstrated the highest sensitivity, which may reflect its use of partially-randomized adapter sequences, but overall performance was lower than the QIAseq and TailorMix kits. NEBNext showed intermediate performance. We reaffirm that biases are kit specific, complicating the comparison of miRNA datasets generated using different kits.